Assessing the role of traditional land management practices in improving cropland productivity: The case of Diga Woreda, Oromia - Megersa, T. (Ambo University, 2011)
A Land management practice has many forms and the focus of this research is on traditional land management practices. The main objective of this study was to assess the role of traditional land management practices in improving cropland productivity in the study area. The study was mainly focused on describing the soil fertility status between lands with and without traditional land management practices.12 Soil sample was taken from farmland with four and above practices and another 12 soil sample from farmland without practices at the distance of less than 2km.The sample were compared for its soil quality, crop biomass weight and yield.. Multistage sampling technique was used to select peasant association, cultivated fields for soil sampling and households for questionnaire survey. Transects were used to collect soil samples and structured and semi-structured questionnaires to gather the necessary information from the sampled households, key informants and group discussions. The results of soil chemical property analysis revealed that, the status of soil organic matter, total nitrogen, available phosphorous, available potassium, cation exchange capacity and pH of the soil with traditional land management practices recorded the highest mean value ranging from 5 to 40 per cent than soil without traditional land management practices. Furthermore, dry biomass weight and crop yield in land with traditional practices has showed a greater mean value as compared to soil without practices. The traditional land management practices improved cropland productivity through addition of organic matter to the soil, adding nitrogen, maintaining organic matter and plant nutrients, and improving soil structures increasing water infiltration and reducing run off. The decline in fertility of the soil without the practices might was due to the removal of plant nutrient by erosion and crop harvest without replacement. The Majority of the farmers (68 to 95%) reported that combinations of practices are very effective in improving cropland productivity.